Trends of Fast Food among University Students - Khairunesa ISA; Asliaty ATIM (Communications of International Proceedings, 2020)
The trend of students’ food selection today has changed in line with the prevailing development. Food is no longer seen as only a necessity in life, but it also reflects the social status of students that sadly manages to overrule health issues and academic achievements. This study was conducted to examine the student literacy level on the effects of fast food consumption and the trend of fast food intake among students of University A. The results from the analysis found that the student literacy level on the effects of fast food intake was high with a mean value of 4.27 and most students only consumed fast food as snacks in the evening at their own residences. This fast food consumption trend shows that students did not consider fast food as their main meals but only as their light meals or snacks.
Keywords: food literacy; food consumption; fast food; academic performance.